Gnoseological Properties and Antecedents of Modern and Contemporary Gnosticism. A Critical Analysis based on Eric Voegelin’s Thought - Buzeta Undurraga, Sebastián (2023)
The gnostic presence denounced by Voegelin at the end of the last century —a presence which has seen its more faithful expression in contemporary ideologies— has mutated into several manifestations denounced by contemporary thinkers, not only because of their immanent nature, but also due to their gnoseological inconsistency. Thus, this paper aims to offer a deeper study of the fundamental properties and characteristics of modern and contemporary Gnosticism, as well as of its gnoseological antecedents. In order to do this, I focus, first, on a critical analysis of the characteristics of gnostic thought, taking mainly Vogelin’s ideas as a starting point. After this I analyse the antecedents of gnostic thought in the theological reflections of Joachim of Fiore and the nominalism of William of Ockham.